INNOVATIVE METHODS IN TEACHING SPORTS SCIENCES IN HIGHER EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines innovative methods in teaching sports sciences within the context of higher education institutions in Uzbekistan. The integration of modern pedagogical strategies and digital tools is increasingly seen as essential for equipping students with both theoretical knowledge and practical competencies. The study emphasizes the importance of interactive, student-centered approaches, such as problem-based learning, blended learning models, and the use of simulation technologies. These innovations aim to enhance learners’ motivation, critical thinking, and professional readiness in a field that continuously evolves in response to technological and scientific advancements. The article also considers the institutional and infrastructural challenges faced by higher education establishments in implementing these methods and offers recommendations for addressing them. By aligning educational practices with global trends and national educational reforms, sports sciences education can better meet the demands of the 21st century.